From the phenomena of sound relief Delete the nun in the old Arabic poetry in the light of the modern audio lesson - al- Awamat, Khaled Fahad (Journal of Humanities & Social Sciences, 2019)
This research seeks to discuss the phenomenon of sound in the ancient Arabic poetry, the phenomenon of the deletion of Nun; for the mitigation of voice, which is subject to other language phenomena to the laws of sound. In order to achieve the objective of the study, the researcher began to monitor this phenomenon from its primary sources and follow it in the old linguistic explanations and analyze it in accordance with the data of the modern sound laws, which are based on the law of mitigation, ease and facilitation Acceptable justification, without prejudice to the meaning of the word in which the deletion occurred.